Metabolic profiles and morphological characteristics of leaf tips among different sweet potato (Ipomoea batatas Lam.) varieties - Wenqing Tan; Xinbo Guo; Zhangying Wang; Rong Zhang; Chaochen Tang; Bingzhi Jiang; Ruixue Jia; Yuanyuan Deng; Shaohai Yang; Jingyi Chen (Journal of Integrative Agriculture)
Sweet potato leaf tips have high nutritional value, and exploring the differences in the metabolic profiles of leaf tips among different sweet potato varieties can provide information to improve their qualities. In this study, a UPLC-Q-Exactive Orbitrap/MS-based untargeted metabolomics method was used to evaluate the metabolites in leaf tips of 32 sweet potato varieties. Three varieties with distinct overall metabolic profiles (A01, A02, and A03), two varieties with distinct profiles of phenolic acids (A20 and A18), and three varieties with distinct profiles of flavonoids (A05, A12, and A16) were identified. In addition, a total of 163 and 29 differentially expressed metabolites correlated with the color and leaf shape of sweet potato leaf tips, respectively, were identified through morphological characterization. Group comparison analysis of the phenotypic traits and a metabolite-phenotypic trait correlation analysis indicated that the color differences of sweet potato leaf tips were markedly associated with flavonoids. Also, the level of polyphenols was correlated with the leaf shape of sweet potato leaf tips, with lobed leaf types having higher levels of polyphenols than the entire leaf types. The findings on the metabolic profiles and differentially expressed metabolites associated with the morphology of sweet potato leaf tips can provide useful information for breeding sweet potato varieties with higher nutritional value.